Population genomics reveals a mismatch between management and biological units in green abalone (Haliotis fulgens) - Mejía-Ruíz, Paulina; Perez-Enriquez, Ricardo; Mares-Mayagoitia, Jorge Alberto; Valenzuela-Quiñonez, Fausto (PeerJ, 2020)
Effective fishery management strategies should be based on stock delimitation and knowledge of the spatial scale at which species are distributed. However, a mismatch often occurs between biological and management units of fishery resources. The green abalone (Haliotis fulgens) supports an important artisanal fishery in the west coast of the Baja California Peninsula (BCP), Mexico, which has shown a declining tendency despite the several management measures. Thus, the aim of this study was to characterize the spatial patterns of neutral genomic variation of green abalone along the BCP to test whether the genomic structure patterns support the current green abalone management areas. To test this hypothesis, a set of 2,170 putative neutral single nucleotide polymorphisms discovered by a double digest restriction-site associated DNA approach was used on 10 locations along the BCP. The results revealed a population structure with three putative groups: Guadalupe Island and northern and southern BCP locations. The contemporary gene flow might be explained by local oceanographic features, where it is bidirectional within the southern region but with a predominant southward flow from the northern region. These findings indicated that the administrative areas did not match the biological units of H. fulgens fishery; hence, the stock assessment and management areas should be revised.
Keywords: Population genomics; Fisheries management; Haliotis fulgens; ddRAD; SNPs; Green abalone; Abalone